Stability enhancement of a self-amplified spontaneous emission free-electron laser with bunching containment - Huaiqian Yi; Xiaofan Wang; Li Zeng; Yifan Liang; Weiqing Zhang (Physical Review Accelerators and Beams)
The self-amplified spontaneous emission (SASE) mechanism, the fundamental operating principle of numerous free-electron laser (FEL) facilities, is driven by electron beam shot noise and leads to significant fluctuations in the output pulse energy. This study presents a robust method for improving pulse energy stability by incorporating a dispersion element that introduces longitudinal dispersion into the electron beam during the exponential growth phase of the SASE process. At this phase, the density modulation of the electron beam, characterized by the bunching factor, undergoes large fluctuations, resulting in substantial variations in the emitted radiation power. The introduction of longitudinal dispersion allows for controlled manipulation of the bunching distribution, suppressing fluctuations and enhancing pulse energy stability. The stabilization mechanism is explained in this paper, and its impact on the radiation properties is analyzed for both the standard SASE scheme and advanced lasing setups, such as a two-stage lasing process for two-color pulse generation, with the initial stage operating in SASE mode.